Urgensi Transparansi Suku Bunga Pada Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi - Ramadhani, Romy Rizqulah; Lyanthi, Merline Eva (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The urgency of interest rate transparency in information technology-based lending services is crucial to protect the legal rights of borrowers. Based on POJK 10/05/2022, transparency is an obligation for fintech organizers, but many parties do not comply with the standards set by AFPI. As a result, borrowers are vulnerable to interest rate abuse. Insufficiently strict regulations and weak supervision and enforcement of sanctions from OJK create legal loopholes that can be exploited by fintech organizers. This study emphasizes the importance of OJK's role in strengthening policies and supervision, as well as enforcing sanctions to ensure compliance with the principle of transparency. This is expected to create a fairer financial services ecosystem, protect consumers, and support sustainable digital economic growth in Indonesia.